Acclimation of consortium of micro-algae help removal of organic pollutants from meat processing wastewater. (20th March 2019) - Hu, Xinjuan; Meneses, Yulie E.; Stratton, Jayne; Wang, Bing
Abstract: The purpose of this study was to acclimate and select microalgae species to efficiently remove organic pollutants from meat processing wastewater while accumulating biomass for further processing. Results showed that C. protothecoides, S. obliquus and C. vulgaris and their consortia presented robust growth in synthesized wastewater. Acclimated S. obliquus, C. vulgaris and C. sorokiniana adapted better to the environment in wastewater and achieved significantly ( P  < 0.05) higher biomass than those without acclimatization. At the end of the nine-day-treatment period, S . obliquus and its consortium with C. vulgaris achieved the highest biomass accumulation (1.7 g/L). However, cultivation periods longer than five days did not significantly ( P  > 0.05) improve the microalgal removal of chemical oxygen demand (COD) and nutrients under conditions evaluated in this study. Results showed that 74% total phosphate (TP-PO4 3- ), 52% total nitrogen (TN) and 87% COD were removed from wastewater after five-day microalgae treatment, which was higher than the removal observed in control samples (48% TP-PO4 3-, 32%TN, 84% COD). Microalgae treatment did not improve COD removal but was able to accelerate the removal rate. A consortium containing three species ( S. obliquus  +  C. vulgaris  +  C. sorokiniana) was assessed to improve nutrients and COD removal. The consortium achieved higher removal of COD (91%), TN (67%) and TP-PO4 3- (69%). Therefore, the acclimated consortium of S. obliquus  +  C. vulgaris + C. sorokiniana can be effectively used in the treatment of heavily polluted meat processing wastewater as primary or secondary treatment option. Highlights: Acclimation significantly helped some microalgae better adapt to harsh environment in food processing wastewater. Selected Microalgae accelerated the removal of organic carbon by bacteria and increased the removal of TN and TP-PO4 3 . Microalga consortium of S. obliquus  +  C. vulgaris  +  C. sorokiniana was selected to treat meat processing wastewater.